PENERAPAN MODEL KOMUNIKASI NONVERBAL GURU UNTUK ANAK BERKEBUTUHAN KHUSUS TUNARUNGU DALAM PENGEMBANGAN KETERAMPILAN KOMUNIKASI - Robert Aji Saputra; Zainal Alim (Al-Amien Prenduan University, Sumenep, 2021)
In general communication is any form of a person's behavior both verbal and nonverbal are responded by others. Communication includes a broader understanding of just dialogue. The problem occurs when looking at the field are many of the children with special needs Deaf who still lack vocabulary so that in communicating sometimes children with special needs Deaf is experiencing obstacles in expressing something they want to express but do not know what vocabulary they will express. From some of the research focus above, there are several achievement objectives in the research that will be studied by researchers: 1. To learn more in depth how the teacher in applying nonverbal communication model for children with special deaf need in developing communication skill at SLB Asih Mulya in Pamekasan. 2. To learn more deeply the forms of nonverbal communication applied in SLB Asih Mulya in Pamekasan. 3. To know the inhibiting factors in the application of nonverbal communication model. Based on the title of this study, the researcher uses a qualitative approach, with data collection procedures using observation techniques, documentation, and interviews. And using data analysis techniques Miles and Hubberman. The researchers take the following conclusions in the application of nonverbal communication model of teachers to children with special deaf needs in the development of communication skills. Namely Some application of nonverbal communication model applied by teachers for children with special deaf need include: Sign language, and Fig. While the forms of nonverbal communication provided to children with special needs deaf: facial, hand, oral, articulation in the mention of vocabulary, lip motion, some kind of miniature of the original objects.Â